Ameloblastoma in a Patient With Williams Syndrome and Use of Fibular Flap - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Williams syndrome (WS, also known as Williams - Beuren syndrome) is a genetic disorder caused by a deletion of large gene locus at chromosome 7q11.23. Its incidence is estimated from 1 in 20,000 to 1 in 50,000.(1) Williams syndrome is characterized by supravalvular aortic stenosis, dysmorphic facial features, teeth abnormalities, neurodevelopmental delay, learning disabilities, and excessively friendly personality.(2) The genetic deletion that is well defined in WS is currently not considered a risk factor for cancer development. 3 However, more than 15 cases of malignancy were reported in patients with WS.(1,3) Here, we described a unique case of WS diagnosed with a mandibular ameloblastoma, its surgical management and successful reconstruction with a vascularized fibular flap. To our knowledge, this is the first report of WS associated with ameloblastoma and first report of free flap reconstruction in a patient with WS in the literature.